2020
DOI: 10.22161/ijaers.75.20
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health and Quality of Life in adults living in Northeastern Brazil

Abstract: Objective: To assess the oral health-related quality of life of adult people regarding social, physical and psychological aspects. Methods: Analytical cross-sectional research conducted with adults living in Northeastern Brazil. Patients were assessed through three questionnaires: Sociodemographic (age, gender, skin color, marital status, education and income); OHIP-14 -instrument that assesses the impact of oral health on quality of life; COHI -Community Oral Health Indicator, which assesses: 1-Masticatory ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…If exposed to s t i m u l i , such as cold, heat, sweet and sour foods, it can cause pain, which can lead to disturbed eating a n d sleeping, inability to work properly, uncontrolled emotions, concentration issues, psychological disturbance, and interference with daily activities. 14 Additionally, this finding is consistent with that of Anbarserri's study which found that tooth loss has a negative impact on a person's quality of life. When the severity of tooth loss increases, the OHIP14 score also increases, which means that the quality of life is in a bad category, indicating higher oral health problems.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…If exposed to s t i m u l i , such as cold, heat, sweet and sour foods, it can cause pain, which can lead to disturbed eating a n d sleeping, inability to work properly, uncontrolled emotions, concentration issues, psychological disturbance, and interference with daily activities. 14 Additionally, this finding is consistent with that of Anbarserri's study which found that tooth loss has a negative impact on a person's quality of life. When the severity of tooth loss increases, the OHIP14 score also increases, which means that the quality of life is in a bad category, indicating higher oral health problems.…”
Section: Discussionsupporting
confidence: 90%
“…As a result, they may unconsciously limit nutritional intake. 5,14 The quality of life in the poor category was mostly found in females. This research is in line with research conducted by Utami which found that the quality of life of males is better than that of females, which may indicate that females experience a more severe impact of oral disorders than males.…”
Section: Discussionmentioning
confidence: 99%